Analisis Keterlambatan Proyek Konstruksi di PT. PLN (Persero) UIP Sumbagut - Irwan Irwan; Melloukey Ardan; Nuril Mahda Rangkuti; Febrina Monalisa (Universitas Medan Area, 2022)
Project delays are the main contribution to project cost overruns. The research intends to determine the main factor that cause delays in construction projects at PT. PLN (PERSERO) UIP Sumbagut. In this research, there were 31 variables which were grouped into 6 categories. The research is done by distributing questionnaires to 20 respondents from the owner who also handles the project. The data analysis used a comparison of the percentage, rank mean and standard deviation which were analyzed with Statistical Product and Service Solutions (SPSS). Based on the results of data analysis, it was found that the main factor causing delays in construction projects at PT. PLN (PERSERO) UIP Sumbagut is a shortage of manpower to complete a project. In addition, there are several other dominant factors, namely labor qualifications that do not meet standards; difficulties in financial cash flow and project funding from contractors; scheduling conflicts with sub-contractors and suppliers in the completion of work; security disturbances during the project.